2018
DOI: 10.3390/ijerph15040632
|View full text |Cite
|
Sign up to set email alerts
|

Burden and Risk Factors for Cold-Related Illness and Death in New York City

Abstract: Exposure to cold weather can cause cold-related illness and death, which are preventable. To understand the current burden, risk factors, and circumstances of exposure for illness and death directly attributed to cold, we examined hospital discharge, death certificate, and medical examiner data during the cold season from 2005 to 2014 in New York City (NYC), the largest city in the United States. On average each year, there were 180 treat-and-release emergency department visits (average annual rate of 21.6 per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 21 publications
3
24
0
Order By: Relevance
“…Between January 1, 2009, and July 31, 2019, there were 139 hypothermia‐related deaths in NYC with an annualized mortality rate of 1.7 per million. This is consistent with recently published studies (10) and considerably lower than the 2003–2013 national average with unadjusted annual rates ranging from 0.3 to 0.5 per 100,000 persons (or 3–5 per million) (11). Houston experienced fewer deaths ( n = 50) but had a higher annualized mortality rate at 2.4 per million, again lower than the national average.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Between January 1, 2009, and July 31, 2019, there were 139 hypothermia‐related deaths in NYC with an annualized mortality rate of 1.7 per million. This is consistent with recently published studies (10) and considerably lower than the 2003–2013 national average with unadjusted annual rates ranging from 0.3 to 0.5 per 100,000 persons (or 3–5 per million) (11). Houston experienced fewer deaths ( n = 50) but had a higher annualized mortality rate at 2.4 per million, again lower than the national average.…”
Section: Discussionsupporting
confidence: 93%
“…Hypothermia‐related death is associated with advanced age, the male sex, comorbidities such as cardiovascular disease and pulmonary disease, homelessness, and intoxication (5,10–15). The most common comorbidities among decedents in our review were cardiovascular disease, pulmonary disease, and mental illness.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that a lower BMI indicates less adipose tissue and less protection against cold exposure; thus, a low BMI could contribute to the development of chilblains [ 31 ]. A US study reviewed medical records and death certificates during the cold season in New York to identify risk factors for cold-related illnesses and deaths [ 32 ]. The data showed that decedents were significantly more likely to be normal or underweight than the general population (58% vs. 43%, p ≤ 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that 25% of all hypothermic injuries and 20% of hypothermic deaths were attributed to individuals experiencing homelessness. A recent study in New York reported a similar proportion of deaths (18%) and hospital admissions (24%) to occur among individuals who were homeless; yet, only 1% of ED visits were attributed to homeless individuals [11].…”
Section: Discussionmentioning
confidence: 99%
“…Emergency department (ED) visits and hospital admissions for hypothermia could be very resource-intensive and often disproportionately represent individuals from disadvantaged groups [9,10]. For instance, individuals who experienced homelessness accounted for 1% of the ED visits, 24% of the hospitalizations, and 18% of the deaths attributed to hypothermia in New York City between 2005 and 2014 [11]. Further, individuals who were homeless in Poland had a nearly 13-times higher risk of death from hypothermia than individuals from the general population [12].…”
Section: Introductionmentioning
confidence: 99%